P0441CONCOMITANT MEDICATIONS OR IMMUNE CHECHKPOINT INHIBITOR, WHO IS THE CAUSE OF ACUTE TUBULOINTERSTITIAL NEPHRITIS IN IMMUNOTHERAPY?. (6th June 2020) - ANTON PAMPOLS, PAULA; Martinez Valenzuela, Laura; Draibe, Juliana; Coloma, Ana; Fulladosa, Xavier; Torras, Joan
Abstract: Background and Aims: During the last decades, the incidence of drug-associated acute tubulointerstitial nephritis (ATIN) has markedly increased. In the recent years, immune checkpoint inhibitors (ICI) have shown promising results in the treatment of malignancies such as melanoma or lung cancer. Immune mediated adverse events are frequent during the use of these drugs as a result of their mechanism of action. The most common kidney lesion in ICI-treated patients who present acute kidney injury (AKI) is ATIN. It is well established that classical drug-induced ATIN is an allergic drug hypersensitivity reaction mediated by T lymphocytes that occurs 7-10 days after exposure. On the contrary, the pathomechanism of ICI-related ATIN remains controversial. Together with the hypothesis that ATIN is a hypersensitivity reaction against ICI itself, other authors propose that loss of inhibition of T cells may facilitate hypersensitivity reactions to previously tolerated drugs or kidney antigens. Method: We reviewed 3 cases of ICI-associated ATIN diagnosed in our nephrology unit with known concomitant medications associated to ATIN. The main demographical, clinical and analytical variables such as gender, age, type of malignancy and oncological treatment were recorded. Results: Patient 1: A 70 year-old man was diagnosed with a non-small-cell lung carcinoma in June 2018. He was treated with carboplatin, paclitaxel and nivolumab (first cycle 21 st June 2018), and underwent lobectomy. NSAIDs were prescribed on September 2018 after surgery. Creatinine was normal at baseline. On September 2018 (110 days after nivolumab initiation and 7 days after NSAIDs prescription) he was admitted to the nephrology unit due to AKI, and the kidney biopsy revealed ATIN. ICI and NSAIDs were discontinued. He was treated with steroids with partial renal recovery. Patient 2: An 82 year-old man was diagnosed with a locally advanced nasal melanoma. He was treated with pembrolizumab. He was referred to the emergency room 73 days after pembrolizumab initiation presenting acute renal failure. Immunological tests were negative and ultrasonography was normal. No other ATIN-related drugs were identified. The final diagnostic was ATIN confirmed by kidney biopsy and the patient was treated with steroids. ICI was discontinued and the recovery of the kidney function was partial. Six months later he was diagnosed with septic arthritis on his right wrist due to Pseudomonas aeruginosa. 7 days after ciprofloxacin prescription he presented AKI. The diagnosis was a flare of interstitial nephritis, thus oral steroids were re-initiated. Kidney function partially recovered. Patient 3: A 63-year-old woman was diagnosed of renal cancer diagnosed in 2014. She was initially treated with Sunitinib, but it was discontinued due to hypothyroidism. She initiated second-line treatment with Nivolumab 7 months before referral to our nephrology unit. Baseline creatinine was normal. 5 days before referral, she took 3 pills of ibuprofen 600mg during three days due to knee pain. The final diagnostic according to kidney biopsy was ATIN. ICI and NSAIDs were discontinued and she was treated with steroids. Kidney function was totally recovered. Conclusion: ICI associated ATIN present scarce temporal association with the initiation of ICI. High prevalence of use of other ATIN-related drugs has been noticed among these patients. Herein, we report 3 cases of ATIN in the setting of the treatment with ICI. The temporal association of the first episode with other drugs rather than ICI, and the relapse after the rechallenge with a drug classically associated with ATIN suggests that it might be caused by these drugs rather than by ICI itself, that actually may facilitate the drug hypersensitivity reaction. Research in the pathomechanisms of ATIN in ICI patients is required in order to anticipate, prevent and treat this adverse effect.